Monitoring dan Notifikasi Crust Breaker pada Tungku Reduksi - Muhammad Iqbal Imanuddin Abbas; Hadi Supriyanto; Nuryanti Nuryanti (JTRM (Jurnal Teknologi dan Rekayasa Manufaktur), 2025)
Crust Breaker is an equipment in aluminum reduction furnace that functions to break the crust on the electrolyte surface. So far, the operational team has identified abnormal crust breakers manually because there is no abnomal crust breaker detection tool available. For this reason, the tool to detect when an abnormal crust breaker occurs is designed by making a prototype crust breaker and measuring the implementation directly on the reduction furnace which can be monitored in real time through the website and providing notifications when abnormal crust breaker conditions occur via Telegram, as well as adding light and buzzer indications in the room. The results showed that the use of toggle switches with normal crust breaker conditions got an average detection response of 86.54% and abnormal crust breaker conditions got an average detection response of 90.51%, as well as direct implementation testing on a reduction furnace with a time setting of less than 10 minutes, the crust breaker provided an actual notification of not touching the electrolyte. Based on these results, the right time to ensure the condition of the abnormal crust breaker is ≥10 minutes.